A wear-resistant hard alloy and its preparation method and application

By adding high-entropy alloy powder, carbon nanotubes, titanium aluminum carbide and tantalum carbide to cemented carbide, the problem of insufficient wear resistance of existing cemented carbides has been solved, and the wear resistance and mechanical properties of cemented carbides have been significantly improved, and it is suitable for cutting tools and drill bits and other applications.

CN119287239BActive Publication Date: 2025-04-01ZHUZHOU MINGRI CEMENTED CARBIDE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411770268.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-01
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing cemented carbide has shortcomings in wear resistance and is prone to wear and breakage.

Method used

A wear-resistant cemented carbide is used, and its composition includes 78.4~87.9 parts of tungsten carbide powder, 4~12 parts of high-entropy alloy powder, 2~8 parts of carbon nanotubes, 1~6 parts of titanium aluminum carbide, and 0.1~0.6 parts of tantalum carbide. Through the combined action of high-entropy alloy powder, carbon nanotubes, titanium aluminum carbide, and tantalum carbide, the wear resistance and mechanical properties of cemented carbide are significantly improved.

Benefits of technology

It significantly improves the wear resistance and mechanical properties of cemented carbide, and can be effectively applied in cutting tools, drill bits and other fields, extending the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a wear-resistant cemented carbide and a preparation method and application thereof, belonging to the technical field of cemented carbide, comprising the following components in parts by weight: 78.4-87.9 parts of tungsten carbide powder, 4-12 parts of high entropy alloy powder, 2-8 parts of carbon nanotubes, 1-6 parts of titanium aluminum carbide, and 0.1-0.6 parts of tantalum carbide; the high entropy alloy powder comprises the following components in parts by weight: 1-3 parts of manganese powder, 2-5 parts of silicon powder, 5-12 parts of chromium powder, 10-15 parts of carbon powder, 10-15 parts of cobalt powder, 10-18 parts of molybdenum powder, and 40-50 parts of nickel powder; the tungsten carbide powder comprises a first tungsten carbide powder and a second tungsten carbide powder in a weight ratio of (2-4):1. The invention uses tungsten carbide powder as a matrix, and the high entropy alloy powder, carbon nanotubes, titanium aluminum carbide, and tantalum carbide work together to significantly improve the wear resistance and mechanical properties of the cemented carbide, and can be well applied to the preparation of cutting tools and drill bits, and has a wide range of application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cemented carbide, and in particular to a wear-resistant cemented carbide and a preparation method and application thereof. Background Art

[0002] Wear-resistant cemented carbide is a composite material made of hard carbide (such as tungsten carbide, titanium carbide, etc.) and metal binder (such as cobalt, nickel, etc.) sintered at high temperature. Due to its excellent strength and toughness, it is widely used in cutting tools, molds and other fields.

[0003] At present, the main components of cemented carbide include carbides (such as tungsten carbide, titanium carbide, etc.) and bonding metals (such as cobalt, nickel, etc.). Traditional cemented carbide usually uses carbide powder of a single particle size as the main component. Although it performs well in terms of hardness, it lacks wear resistance and is prone to wear and breakage.

[0004] In view of this, this application is filed. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a wear-resistant cemented carbide and a preparation method and application thereof. The cemented carbide has excellent wear resistance and mechanical properties and can be well applied to cutting tools and drill bits.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A wear-resistant hard alloy comprises the following components in parts by weight: 78.4 to 87.9 parts of tungsten carbide powder, 4 to 12 parts of high entropy alloy powder, 2 to 8 parts of carbon nanotubes, 1 to 6 parts of titanium carbide aluminum, and 0.1 to 0.6 parts of tantalum carbide;

[0008] The high entropy alloy powder comprises the following components in parts by weight: 1 to 3 parts of manganese powder, 2 to 5 parts of silicon powder, 5 to 12 parts of chromium powder, 10 to 15 parts of carbon powder, 10 to 15 parts of cobalt powder, 10 to 18 parts of molybdenum powder, and 40 to 50 parts of nickel powder;

[0009] The tungsten carbide powder includes a first tungsten carbide powder and a second tungsten carbide powder in a weight ratio of (2-4):1, the average particle size of the first tungsten carbide powder is 400-500 nm, and the average particle size of the second tungsten carbide powder is 1-3 μm.

[0010] The present invention creatively combines the above-mentioned raw materials, takes tungsten carbide powder as the matrix, and works together with high entropy alloy powder, carbon nanotubes, titanium carbide, and tantalum carbide to significantly improve the wear resistance and mechanical properties of cemented carbide. It can be well used in the preparation of cutting tools and drill bits, and has broad application prospects.

[0011] Among them, the multi-components of the high entropy alloy powder described above have high mixing entropy, which makes the crystal structure of the material more complex, enhances the solid solution strengthening effect of the alloy, promotes the formation of a more uniform microstructure, can effectively resist wear and reduce fatigue damage; carbon nanotubes (CNTs) have a unique tubular structure, and their interface interaction with high entropy alloy powder and tungsten carbide powder plays an excellent strengthening role, which can significantly improve the strength and toughness of the composite material, disperse stress when subjected to force, and effectively reduce stress concentration; the composite of TiC and Al in titanium aluminum carbide can form a phase with excellent hardness, which can significantly improve the wear resistance of cemented carbide; the addition of titanium aluminum carbide can improve the fracture toughness of cemented carbide, and by forming finer and more dispersed particles, it plays a "bridge" role, effectively alleviating the problem of reduced toughness caused by excessive hardness. When high entropy alloy powder, carbon nanotubes, and titanium aluminum carbide exist together, they can form a multiphase composite material and produce a significant synergistic effect. High entropy alloy powder mainly provides a complex solid solution structure, CNTs mainly improve the strength and toughness of the material by enhancing interface bonding, and titanium aluminum carbide mainly supplements the performance of the matrix by improving hardness and wear resistance. The three interact and cooperate with each other. The combination of different phases can achieve interaction, which can effectively alleviate stress concentration, extend the service life of the material, and significantly improve the wear resistance and mechanical properties of the alloy.

[0012] The present invention uses two tungsten carbide powders of different particle sizes, and the particle size ratio between the two is 2-7.5; it can effectively optimize the particle distribution of the system, help to improve density, reduce porosity, reduce grain growth during sintering, promote grain refinement, help to form a more uniform microstructure, and promote the formation of a more uniform and dense crystal structure. The mutual filling of the first tungsten carbide powder and the second tungsten carbide powder and other components can reduce the contact area and reduce the wear rate, thereby improving wear resistance. In addition, the wear debris formed by the finer tungsten carbide particles during the friction process is relatively small, which helps to reduce the wear rate, while assisting in dispersing stress, further reducing stress concentration, thereby significantly improving the wear resistance and mechanical properties of the alloy.

[0013] As a preferred embodiment of the present invention, the following components are included in weight parts: 81.8~86.6 parts of tungsten carbide powder, 6~10 parts of high entropy alloy powder, 3~5 parts of carbon nanotubes, 2~5 parts of titanium carbide aluminum, and 0.2~0.4 parts of tantalum carbide. Especially when the amount of each raw material is within this range, the synergistic effect is more obvious, which can further improve the wear resistance and mechanical properties.

[0014] As a preferred embodiment of the present invention, the specific surface area of ​​the first tungsten carbide powder is 45-46 m 2 / g, the volume density of the first tungsten carbide powder is 3.4~3.6g / cm 3 .

[0015] As a preferred embodiment of the present invention, the specific surface area of ​​the second tungsten carbide powder is 19.1~21m 2 / g, the volume density of the second tungsten carbide powder is 4.9-5.6g / cm 3 .

[0016] As a preferred embodiment of the present invention, the weight ratio of the sum of the weight of the high entropy alloy powder and titanium aluminum carbide to the carbon nanotubes is (3-13):3.

[0017] As a preferred embodiment of the present invention, the preparation method of the high entropy alloy powder is: manganese powder, silicon powder, chromium powder, carbon powder, cobalt powder, molybdenum powder, and nickel powder are evenly mixed, and ball milled at a speed of 400-800 rpm for 6-12 hours to obtain high entropy alloy powder.

[0018] Among them, the average particle size of the manganese powder is 0.5~10μm; the average particle size of the silicon powder is 0.5~10μm; the average particle size of the chromium powder is 0.5~10μm; the average particle size of the carbon powder is 0.5~10μm; the average particle size of the cobalt powder is 0.5~10μm; the average particle size of the molybdenum powder is 0.5~10μm; and the average particle size of the nickel powder is 0.5~10μm.

[0019] As a preferred embodiment of the present invention, the average particle size of the titanium aluminum carbide is 200-400 meshes.

[0020] As a preferred embodiment of the present invention, the outer diameter of the carbon nanotube is 10-20 nm, and the length is 10-20 μm.

[0021] The present invention also provides a method for preparing wear-resistant cemented carbide, comprising the following steps:

[0022] Tungsten carbide powder, high entropy alloy powder, carbon nanotubes, titanium aluminum carbide and tantalum carbide are wet-milled and mixed uniformly, pressed into shape, and sintered to obtain wear-resistant hard alloy;

[0023] The sintering temperature is 1450-1480° C., and the sintering time is 2-4 hours.

[0024] The wet ball milling is conventional wet ball milling in the art, using anhydrous ethanol as the ball milling medium, and the amount of anhydrous ethanol used is 100-300 mL / kg.

[0025] The pressing pressure is 150-250 MPa, and the pressing time is 8-20 min.

[0026] The invention also provides an application of the wear-resistant hard alloy in the preparation of cutting tools and drill bits.

[0027] The beneficial effects of the present invention are: (1) The present invention combines the above-mentioned raw materials, takes tungsten carbide powder as the matrix, and works together with high entropy alloy powder, carbon nanotubes, titanium aluminum carbide, and tantalum carbide to significantly improve the wear resistance and mechanical properties of cemented carbide, which can be well used in the preparation of cutting tools and drill bits, and has broad application prospects.

[0028] (2) The multi-component high entropy alloy powder described in the present invention has a high mixing entropy, which makes the crystal structure of the material more complex, enhances the solid solution strengthening effect of the alloy, promotes the formation of a more uniform microstructure, can effectively resist wear and reduce fatigue damage; carbon nanotubes (CNTs) have a unique tubular structure, and their interface interaction with high entropy alloy powder and tungsten carbide powder plays an excellent strengthening role, which can significantly improve the strength and toughness of the composite material, disperse stress when subjected to force, and effectively reduce stress concentration; the composite of TiC and Al in titanium aluminum carbide can form a phase with excellent hardness, which can significantly improve the wear resistance of cemented carbide; the addition of titanium aluminum carbide can improve the fracture toughness of cemented carbide, and by forming finer and more dispersed particles, it plays a "bridge" role, effectively alleviating the problem of reduced toughness caused by excessive hardness. When high entropy alloy powder, carbon nanotubes, and titanium aluminum carbide exist together, they can form a multiphase composite material and produce a significant synergistic effect. High entropy alloy powder mainly provides a complex solid solution structure, CNTs mainly improve the strength and toughness of the material by enhancing interface bonding, and titanium aluminum carbide mainly supplements the performance of the matrix by improving hardness and wear resistance. The three interact and cooperate with each other. The combination of different phases can achieve interaction, which can effectively alleviate stress concentration, extend the service life of the material, and significantly improve the wear resistance and mechanical properties of the alloy. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0030] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0031] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0032] The raw materials used in the embodiments and comparative examples are described as follows:

[0033] Tungsten carbide powder-1: average particle size 400nm, specific surface area 46m 2 / g, volume density is 3.4g / cm 3 , from Ningbo Beijiaer New Materials, brand B-WC-400N.

[0034] Tungsten carbide powder-2: average particle size 500nm, specific surface area 45m 2 / g, volume density is 3.6g / cm 3 , from Ningbo Beijiaer New Materials, brand B-WC-500N.

[0035] Tungsten carbide powder-3: average particle size 300nm, specific surface area 46.5m 2 / g, volume density is 3.2g / cm 3 , from Ningbo Beijiaer New Materials, brand B-WC-300N.

[0036] Tungsten carbide powder-4: average particle size 800nm, specific surface area 40.1m 2 / g, volume density is 4.1g / cm 3 , from Ningbo Beijiaer New Materials, brand B-WC-800N.

[0037] Tungsten carbide powder-5: average particle size 1μm, specific surface area 21m 2 / g, volume density is 4.9g / cm 3 , from Ningbo Beijiaer New Materials, brand B-WC-1W.

[0038] Tungsten carbide powder-6: average particle size 3μm, specific surface area 19.1m 2 / g, volume density is 5.6g / cm 3 , from Ningbo Beijiaer New Materials, brand B-WC-3W.

[0039] Tungsten carbide powder-7: average particle size 5μm, specific surface area 18.6m 2 / g, volume density is 6.9g / cm3 , from Ningbo Beijiaer New Materials, brand B-WC-5W.

[0040] Manganese powder: The average particle size is 1 μm, from Shanghai Xiangtian Nano, brand XT-Mn-01.

[0041] Silicon powder: The average particle size is 1 μm, from Shanghai Xiangtian Nano, brand XT-Si-05.

[0042] Chromium powder: The average particle size is 1 μm, from Shanghai Xiangtian Nano, brand XT-Cr-01.

[0043] Carbon powder: The average particle size is 1 μm, from Shanghai Xiangtian Nano, brand XT-C-6.

[0044] Cobalt powder: The average particle size is 1 μm, from Shanghai Xiangtian Nano, brand XT-Co-05.

[0045] Molybdenum powder: The average particle size is 1 μm, from Shanghai Xiangtian Nano, brand XT-Mo-04.

[0046] Nickel powder: The average particle size is 1 μm, from Shanghai Xiangtian Nano, brand XT-Ni-07.

[0047] Titanium aluminum carbide (Ti3AlC2): 325 mesh, Brofos Nanotech, brand Brofos-TiAlC-2.

[0048] Carbon nanotube-1: outer diameter is 10~20nm, length is 10~20μm, Chengdu Organic Chemistry, Chinese Academy of Sciences, brand TNVM3.

[0049] Carbon nanotube-2: outer diameter is 50~100nm, length is 1~5μm, Chengdu Organic Chemistry, Chinese Academy of Sciences, brand TNFN-8.

[0050] Carbon nanotube-3: outer diameter is 1~2nm, length is 1~3μm, Chengdu Organic Chemistry, Chinese Academy of Sciences, brand TNSSH.

[0051] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.

[0052] The following examples are provided to facilitate understanding of the present invention. These examples are not provided to limit the scope of the claims.

[0053] Example 1

[0054] A wear-resistant hard alloy comprises the following components in parts by weight: 83.7 parts of tungsten carbide powder, 9 parts of high entropy alloy powder, 4 parts of carbon nanotube-1, 3 parts of titanium carbide aluminum, and 0.3 parts of tantalum carbide.

[0055] The preparation method of the high entropy alloy powder is as follows: 12 parts of carbon powder, 10 parts of chromium powder, 4 parts of silicon powder, 2 parts of manganese powder, 15 parts of tantalum powder, 12 parts of cobalt powder, and 45 parts of nickel powder are weighed according to a weight ratio, the manganese powder, silicon powder, chromium powder, carbon powder, cobalt powder, molybdenum powder, and nickel powder are evenly mixed, and ball milled at a speed of 500 rpm for 10 hours to obtain a high entropy alloy powder.

[0056] The tungsten carbide powder includes tungsten carbide powder-1 and tungsten carbide powder-5, and the weight ratio of the tungsten carbide powder-1 to the tungsten carbide powder-5 is 3:1.

[0057] The weight ratio of the sum of the weights of the high entropy alloy powder and titanium aluminum carbide to the carbon nanotubes is 9:3 (for the convenience of comparison in the following text, 12:4 is converted to 9:3).

[0058] The preparation method of the wear-resistant hard alloy comprises the following steps: wet-milling tungsten carbide powder, high entropy alloy powder, carbon nanotubes, titanium aluminum carbide and tantalum carbide at a rotation speed of 200 rpm for 48 hours (the ball milling medium is anhydrous ethanol, and the amount of anhydrous ethanol used is 200 mL / kg), pressing at a pressure of 200 MPa for 10 minutes, and sintering at 1460° C. for 3 hours to obtain the wear-resistant hard alloy.

[0059] Example 2

[0060] The difference between Example 2 and Example 1 is that the amount of each raw material is different, and the others are the same.

[0061] A wear-resistant hard alloy comprises the following components in parts by weight: 86.6 parts of tungsten carbide powder, 6 parts of high entropy alloy powder, 5 parts of carbon nanotube-1, 2 parts of titanium carbide aluminum, and 0.4 parts of tantalum carbide.

[0062] Example 3

[0063] The difference between Example 3 and Example 1 is that the amount of each raw material is different, and the others are the same.

[0064] A wear-resistant hard alloy comprises the following components in parts by weight: 81.8 parts of tungsten carbide powder, 10 parts of high entropy alloy powder, 3 parts of carbon nanotube-1, 5 parts of titanium carbide aluminum, and 0.2 parts of tantalum carbide.

[0065] Example 4

[0066] The difference between Example 4 and Example 1 is that the amount of each raw material is different, and the others are the same.

[0067] A wear-resistant hard alloy comprises the following components in parts by weight: 87.9 parts of tungsten carbide powder, 4 parts of high entropy alloy powder, 2 parts of carbon nanotube-1, 6 parts of titanium carbide aluminum, and 0.1 part of tantalum carbide.

[0068] Example 5

[0069] The difference between Example 5 and Example 1 is that the amount of each raw material is different, and the others are the same.

[0070] A wear-resistant hard alloy comprises the following components in parts by weight: 78.4 parts of tungsten carbide powder, 12 parts of high entropy alloy powder, 8 parts of carbon nanotube-1, 1 part of titanium carbide aluminum, and 0.6 parts of tantalum carbide.

[0071] Example 6

[0072] The difference between Example 6 and Example 1 is that the amount of high entropy alloy powder, carbon nanotube-1, and titanium aluminum carbide is changed (for single comparison, the total amount of the three remains unchanged), thereby changing the weight ratio of the sum of the weights of high entropy alloy powder and titanium aluminum carbide to the carbon nanotubes, while everything else is the same.

[0073] A wear-resistant hard alloy comprises the following components in parts by weight: 83.7 parts of tungsten carbide powder, 9.5 parts of high entropy alloy powder, 3 parts of carbon nanotube-1, 3.5 parts of titanium carbide aluminum, and 0.3 parts of tantalum carbide.

[0074] The weight ratio of the sum of the weight of the high entropy alloy powder and titanium aluminum carbide to the carbon nanotubes is 13:3.

[0075] Example 7

[0076] The difference between Example 7 and Example 1 is that the weight ratio of the sum of the weight of the high entropy alloy powder and titanium aluminum carbide to the carbon nanotubes is changed by changing the amount of high entropy alloy powder, carbon nanotube-1, and titanium aluminum carbide (for a single comparison, the total amount of the three remains unchanged), while the other factors are the same.

[0077] A wear-resistant hard alloy comprises the following components in parts by weight: 83.7 parts of tungsten carbide powder, 7.5 parts of high entropy alloy powder, 6 parts of carbon nanotube-1, 2.5 parts of titanium carbide aluminum, and 0.3 parts of tantalum carbide.

[0078] The weight ratio of the sum of the weight of the high entropy alloy powder and titanium aluminum carbide to the carbon nanotubes is 5:3.

[0079] Example 8

[0080] The difference between Example 8 and Example 1 is that the amount of high entropy alloy powder, carbon nanotube-1, and titanium aluminum carbide is changed (for single comparison, the total amount of the three remains unchanged), thereby changing the weight ratio of the sum of the weights of high entropy alloy powder and titanium aluminum carbide to the carbon nanotubes, while everything else is the same.

[0081] A wear-resistant hard alloy comprises the following components in parts by weight: 83.7 parts of tungsten carbide powder, 10 parts of high entropy alloy powder, 2 parts of carbon nanotube-1, 4 parts of titanium carbide aluminum, and 0.3 parts of tantalum carbide.

[0082] The weight ratio of the sum of the weight of the high entropy alloy powder and titanium carbide aluminum to the carbon nanotubes is 3:21.

[0083] Example 9

[0084] The difference between Example 9 and Example 1 is that the weight ratio of the sum of the weights of the high entropy alloy powder and titanium aluminum carbide to the carbon nanotubes is changed by changing the amounts of high entropy alloy powder, carbon nanotube-1, and titanium aluminum carbide (for a single comparison, the total amount of the three remains unchanged), while the other factors are the same.

[0085] A wear-resistant hard alloy comprises the following components in parts by weight: 83.7 parts of tungsten carbide powder, 6 parts of high entropy alloy powder, 8 parts of carbon nanotube-1, 2 parts of titanium carbide aluminum, and 0.3 parts of tantalum carbide.

[0086] The weight ratio of the sum of the weight of the high entropy alloy powder and titanium aluminum carbide to the carbon nanotubes is 3:3.

[0087] Example 10

[0088] The difference between Example 10 and Example 1 is that the tungsten carbide powder is different, and the other parts are the same.

[0089] The tungsten carbide powder includes tungsten carbide powder-2 and tungsten carbide powder-6, and the weight ratio of the tungsten carbide powder-2 to the tungsten carbide powder-6 is 3:1.

[0090] Embodiment 11

[0091] The difference between Example 11 and Example 1 is that the tungsten carbide powder is different, and the other parts are the same.

[0092] The tungsten carbide powder includes tungsten carbide powder-1 and tungsten carbide powder-5, and the weight ratio of the tungsten carbide powder-1 to the tungsten carbide powder-5 is 2:1.

[0093] Example 12

[0094] The difference between Example 12 and Example 1 is that the tungsten carbide powder is different, and the other parts are the same.

[0095] The tungsten carbide powder includes tungsten carbide powder-1 and tungsten carbide powder-5, and the weight ratio of the tungsten carbide powder-1 to the tungsten carbide powder-5 is 4:1.

[0096] Example 13

[0097] The difference between Example 13 and Example 1 is that the carbon nanotubes are different, and the other parts are the same.

[0098] In this embodiment, an equal amount of carbon nanotube-2 is used to replace carbon nanotube-1.

[0099] Embodiment 14

[0100] The difference between Example 14 and Example 1 is that the carbon nanotubes are different, and the other parts are the same.

[0101] In this embodiment, an equal amount of carbon nanotube-3 is used to replace carbon nanotube-1.

[0102] Comparative Example 1

[0103] The difference between Comparative Example 1 and Example 1 is that the amount of each raw material used in Comparative Example 1 is not within the scope of the present invention, and the others are the same.

[0104] A wear-resistant hard alloy comprises the following components in parts by weight: 89.95 parts of tungsten carbide powder, 2 parts of high entropy alloy powder, 1 part of carbon nanotube-1, 7 parts of titanium carbide aluminum, and 0.05 parts of tantalum carbide.

[0105] Comparative Example 2

[0106] The difference between Comparative Example 2 and Example 1 is that the amount of each raw material used in Comparative Example 2 is not within the scope of the present invention, and the others are the same.

[0107] A wear-resistant hard alloy comprises the following components in parts by weight: 73.5 parts of tungsten carbide powder, 15 parts of high entropy alloy powder, 10 parts of carbon nanotube-1, 0.5 parts of titanium carbide aluminum, and 1 part of tantalum carbide.

[0108] Comparative Example 3

[0109] The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 does not contain high entropy alloy powder (its amount is replaced by carbon nanotubes and titanium aluminum carbide), and the other contents are the same.

[0110] A wear-resistant hard alloy comprises the following components in parts by weight: 83.7 parts of tungsten carbide powder, 8.5 parts of carbon nanotube-1, 7.5 parts of titanium carbide aluminum, and 0.3 parts of tantalum carbide.

[0111] Comparative Example 4

[0112] The difference between Comparative Example 4 and Example 1 is that Comparative Example 4 does not contain carbon nanotubes (the amount of which is replaced by high entropy alloy powder and titanium aluminum carbide), and the other contents are the same.

[0113] A wear-resistant hard alloy comprises the following components in parts by weight: 83.7 parts of tungsten carbide powder, 11 parts of high entropy alloy powder, 5 parts of titanium carbide aluminum, and 0.3 parts of tantalum carbide.

[0114] Comparative Example 5

[0115] The difference between Comparative Example 5 and Example 1 is that Comparative Example 5 does not contain titanium aluminum carbide (its amount is replaced by high entropy alloy powder and carbon nanotubes), and the rest is the same.

[0116] A wear-resistant hard alloy comprises the following components in parts by weight: 83.7 parts of tungsten carbide powder, 10.5 parts of high entropy alloy powder, 5.5 parts of carbon nanotube-1, and 0.3 parts of tantalum carbide.

[0117] Comparative Example 6

[0118] The difference between Comparative Example 6 and Example 1 is that cobalt powder is used to replace high entropy alloy powder in Comparative Example 6, and the other contents are the same.

[0119] A wear-resistant hard alloy comprises the following components in parts by weight: 83.7 parts of tungsten carbide powder, 9 parts of cobalt powder, 4 parts of carbon nanotube-1, 3 parts of titanium carbide aluminum, and 0.3 parts of tantalum carbide.

[0120] Comparative Example 7

[0121] The difference between Comparative Example 7 and Example 1 is that Comparative Example 7 uses nickel powder to replace the high entropy alloy powder, and the other parts are the same.

[0122] A wear-resistant hard alloy comprises the following components in parts by weight: 83.7 parts of tungsten carbide powder, 9 parts of nickel powder, 4 parts of carbon nanotube-1, 3 parts of titanium carbide aluminum, and 0.3 parts of tantalum carbide.

[0123] Comparative Example 8

[0124] The difference between Comparative Example 8 and Example 1 is that Comparative Example 8 uses cobalt powder and nickel powder to replace the high entropy alloy powder, and the other contents are the same.

[0125] A wear-resistant hard alloy comprises the following components in parts by weight: 83.7 parts of tungsten carbide powder, 4.5 parts of nickel powder, 4.5 parts of cobalt powder, 4 parts of carbon nanotube-1, 3 parts of titanium carbide aluminum, and 0.3 parts of tantalum carbide.

[0126] Comparative Example 9

[0127] The difference between Comparative Example 9 and Example 1 is that the tungsten carbide powder is different, and the other parts are the same.

[0128] The tungsten carbide powder includes tungsten carbide powder-3 and tungsten carbide powder-7, and the weight ratio of the tungsten carbide powder-3 to the tungsten carbide powder-7 is 2:1.

[0129] Comparative Example 10

[0130] The difference between Comparative Example 10 and Example 1 is that the tungsten carbide powder is different, and the other parts are the same.

[0131] The tungsten carbide powder includes tungsten carbide powder-4 and tungsten carbide powder-7, and the weight ratio of the tungsten carbide powder-4 to the tungsten carbide powder-7 is 2:1.

[0132] Test Case

[0133] Wear experiment: Anton Paar THT friction and wear testing machine was used for testing, with a loading force of 20N, a wear time of 100min, a wear speed of 15m / min, and a wear distance of 1500m.

[0134] Bending strength: using universal mechanical testing machine.

[0135] Table 1

[0136]

[0137]

[0138] It can be seen from Table 1 that the cemented carbide of the present invention has excellent wear resistance and mechanical properties, and can be well applied to cutting tools and drill bits.

[0139] By comparing Examples 1 to 5 with Comparative Examples 1 to 2, it can be seen that the present invention significantly improves the wear resistance and mechanical properties by controlling the amount of each raw material to: 78.4 to 87.9 parts of tungsten carbide powder, 4 to 12 parts of high entropy alloy powder, 2 to 8 parts of carbon nanotubes, 1 to 6 parts of titanium carbide aluminum, and 0.1 to 0.6 parts of tantalum carbide.

[0140] By comparing Example 1 with Comparative Examples 3 to 5, it can be seen that under the system of the present invention, the high entropy alloy powder, carbon nanotubes, titanium aluminum carbide, and tantalum carbide described in the present invention have a synergistic effect in improving wear resistance and mechanical properties.

[0141] By comparing Example 1 with Comparative Examples 6 to 8, it can be seen that the high entropy alloy powder of the present invention can significantly improve the wear resistance and mechanical properties.

[0142] By comparing Example 1 with Comparative Examples 9-10, it can be seen that the present invention adopts a first tungsten carbide powder and a second tungsten carbide powder in a weight ratio of (2-4):1, the average particle size of the first tungsten carbide powder is 400-500 nm, and the average particle size of the second tungsten carbide powder is 1-3 μm, which significantly improves the high wear resistance and mechanical properties.

[0143] Comparing Examples 1-3 with Examples 4-5, the present invention further improves the wear resistance and mechanical properties by controlling the amount of each raw material to: 81.8-86.6 parts of tungsten carbide powder, 6-10 parts of high entropy alloy powder, 3-5 parts of carbon nanotubes, 2-5 parts of titanium carbide aluminum, and 0.2-0.4 parts of tantalum carbide.

[0144] By comparing Examples 1, 6, and 7 with Examples 8 to 9, it can be seen that the present invention further improves the wear resistance and mechanical properties by controlling the weight ratio of the sum of the weight of the high entropy alloy powder and the titanium aluminum carbide to the carbon nanotubes to be (3 to 13):3.

[0145] By comparing Example 1 with Examples 13-14, it can be seen that the present invention uses carbon nanotubes with an outer diameter of 10-20 nm and a length of 10-20 μm, which further improves the wear resistance and mechanical properties.

[0146] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A wear-resistant hard alloy, characterized in that: The invention comprises the following components in parts by weight: 78.4 to 87.9 parts of tungsten carbide powder, 4 to 12 parts of high entropy alloy powder, 2 to 8 parts of carbon nanotubes, 1 to 6 parts of titanium carbide aluminum, and 0.1 to 0.6 parts of tantalum carbide; The high entropy alloy powder comprises the following components in parts by weight: 1 to 3 parts of manganese powder, 2 to 5 parts of silicon powder, 5 to 12 parts of chromium powder, 10 to 15 parts of carbon powder, 10 to 15 parts of cobalt powder, 10 to 18 parts of molybdenum powder, and 40 to 50 parts of nickel powder; The tungsten carbide powder includes a first tungsten carbide powder and a second tungsten carbide powder in a weight ratio of (2-4):1, the average particle size of the first tungsten carbide powder is 400-500 nm, and the average particle size of the second tungsten carbide powder is 1-3 μm.

2. The wear-resistant hard alloy according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 81.8 to 86.6 parts of tungsten carbide powder, 6 to 10 parts of high entropy alloy powder, 3 to 5 parts of carbon nanotubes, 2 to 5 parts of titanium carbide aluminum, and 0.2 to 0.4 parts of tantalum carbide.

3. The wear-resistant hard alloy according to claim 1, characterized in that: The specific surface area of ​​the first tungsten carbide powder is 45-46 m 2 / g, the volume density of the first tungsten carbide powder is 3.4~3.6g / cm 3 .

4. The wear-resistant hard alloy according to claim 1, characterized in that: The specific surface area of ​​the second tungsten carbide powder is 19.1-21 m 2 / g, the volume density of the second tungsten carbide powder is 4.9-5.6g / cm 3 .

5. The wear-resistant hard alloy according to claim 1, characterized in that: The weight ratio of the sum of the weight of the high entropy alloy powder and titanium aluminum carbide to the carbon nanotubes is (3-13):

3.

6. The wear-resistant hard alloy according to claim 1, characterized in that: The preparation method of the high entropy alloy powder is as follows: manganese powder, silicon powder, chromium powder, carbon powder, cobalt powder, molybdenum powder and nickel powder are uniformly mixed, and ball milled at a speed of 400-800 rpm for 6-12 hours to obtain the high entropy alloy powder.

7. The wear-resistant hard alloy according to claim 1, characterized in that: The average particle size of the titanium aluminum carbide is 200-400 meshes.

8. The wear-resistant hard alloy according to claim 1, characterized in that: The outer diameter of the carbon nanotube is 10-20 nm, and the length is 10-20 μm.

9. The method for preparing the wear-resistant hard alloy according to any one of claims 1 to 8, characterized in that: The following steps are involved: Tungsten carbide powder, high entropy alloy powder, carbon nanotubes, titanium aluminum carbide and tantalum carbide are wet-milled and mixed uniformly, pressed into shape, and sintered to obtain wear-resistant hard alloy; The sintering temperature is 1450-1480° C., and the sintering time is 2-4 hours.

10. Use of the wear-resistant hard alloy according to any one of claims 1 to 8 in the preparation of cutting tools and drill bits.

Citation Information

Patent Citations

  • Carbon nano-tube-tungsten carbide composite material preparation method

    CN103276269A

  • Wear-resistant hard alloy and preparation method thereof

    CN111809093A